Lung epithelial and myeloid innate immunity in influenza-associated or COVID-19-associated pulmonary aspergillosis: an observational study. Issue 12 (December 2022) - Feys, Simon; Gonçalves, Samuel M; Khan, Mona; Choi, Sumin; Boeckx, Bram; Chatelain, Denis; Cunha, Cristina; Debaveye, Yves; Hermans, Greet; Hertoghs, Marjan; Humblet-Baron, Stephanie; Jacobs, Cato; et al.
Summary: Background: Influenza-associated pulmonary aspergillosis (IAPA) and COVID-19-associated pulmonary aspergillosis (CAPA) affect about 15% of critically ill patients with influenza or COVID-19, respectively. These viral–fungal coinfections are difficult to diagnose and are associated with increased mortality, but data on their pathophysiology are scarce. We aimed to explore the role of lung epithelial and myeloid innate immunity in patients with IAPA or CAPA. Methods: In this observational study, we retrospectively recruited patients who had been admitted to the intensive care unit (ICU) of University Hospitals Leuven, Belgium, requiring non-invasive or invasive ventilation because of severe influenza or COVID-19, with or without aspergillosis, between Jan 1, 2011, and March 31, 2021, whose bronchoalveolar lavage samples were available at the hospital biobank. Additionally, biobanked in vivo tracheobronchial biopsy samples from patients with IAPA or CAPA and invasive Aspergillus tracheobronchitis admitted to ICUs requiring invasive ventilation between the same dates were collected from University Hospitals Leuven, Hospital Network Antwerp (Belgium), and Amiens-Picardie University Hospital (France). We did nCounter gene expression analysis of 755 genes linked to myeloid innate immunity and protein analysis of 47 cytokines, chemokines, and growth factors on the bronchoalveolar lavage samples. Gene expression data were used to infer cell fractions by use of CIBERSORTx, to perform hypergeometric enrichment pathway analysis and gene set enrichment analysis, and to calculate pathway module scores for the IL-1β, TNF-α, type I IFN, and type II IFN (IFNγ) pathways. We did RNAScope targeting influenza virus or SARS-CoV-2 RNA and GeoMx spatial transcriptomics on the tracheobronchial biopsy samples. Findings: Biobanked bronchoalveolar lavage samples were retrieved from 166 eligible patients, of whom 40 had IAPA, 52 had influenza without aspergillosis, 33 had CAPA, and 41 had COVID-19 without aspergillosis. We did nCounter gene expression analysis on bronchoalveolar lavage samples from 134 patients, protein analysis on samples from 162 patients, and both types of analysis on samples from 130 patients. We performed RNAScope and spatial transcriptomics on the tracheobronchial biopsy samples from two patients with IAPA plus invasive Aspergillus tracheobronchitis and two patients with CAPA plus invasive Aspergillus tracheobronchitis. We observed a downregulation of genes associated with antifungal effector functions in patients with IAPA and, to a lesser extent, in patients with CAPA. We found a downregulated expression of several genes encoding proteins with functions in the opsonisation, recognition, and killing of conidia in patients with IAPA versus influenza only and in patients with CAPA versus COVID-19 only. Several genes related to LC3-associated phagocytosis, autophagy, or both were differentially expressed. Patients with CAPA had significantly lower neutrophil cell fractions than did patients with COVID-19 only. Patients with IAPA or CAPA had downregulated IFNγ signalling compared with patients with influenza only or COVID-19 only, respectively. The concentrations of several fibrosis-related growth factors were significantly elevated in the bronchoalveolar lavage fluid from patients with IAPA versus influenza only and from patients with CAPA versus COVID-19 only. In one patient with CAPA, we visualised an active or very recent SARS-CoV-2 infection disrupting the epithelial barrier, facilitating tissue-invasive aspergillosis. Interpretation: Our results reveal a three-level breach in antifungal immunity in IAPA and CAPA, affecting the integrity of the epithelial barrier, the capacity to phagocytise and kill Aspergillus spores, and the ability to destroy Aspergillus hyphae, which is mainly mediated by neutrophils. The potential of adjuvant IFNγ in the treatment of IAPA and CAPA should be investigated. Funding: Research Foundation Flanders, Coronafonds, the Max Planck Society, the Fundação para a Ciência e a Tecnologia, the European Regional Development Fund, "la Caixa" Foundation, and Horizon 2020.